Improving Customer Service: A Case Study of Genting Malaysia - Lee, Ming Zhe; Kee, Daisy Mui Hung; Chan, Kai Yin; Liow, Chee Sien; Chin, Khai Yao; Alkandri, Lamia Adel (Journal of The Community Development in Asia, 2020)
Employees are the core asset of an organization. Dedicated employees are the cornerstone of an organization to achieve organization success. Hence, organizations are concerned with their employee performance as they believe that employee performance will bring a significant impact on organizational performance. Genting Malaysia Berhad (Genting Malaysia) is one of the most popular tourism and entertainment company in Malaysia. Genting Malaysia started its operation in 1980. Genting Malaysia emphasizes on their employee performance as well as their customer service. The paper presents customer service is one of the top priorities of Genting Malaysia and how they have improved customer service over the years. The paper also concludes with some recommendation